Exploiting Extracellular Vesicles Strategies to Modulate Cell Death and Inflammation in COVID-19 - Bortot, Barbara; Romani, Arianna; Ricci, Giuseppe; Biffi, Stefania (Frontiers in Pharmacology, 2022)
The coronavirus disease (COVID-19) is responsible for more than 5 million deaths worldwide, with respiratory failure being the most common clinical presentation. COVID-19 complications still present a considerable burden on healthcare systems, and signs of the post-COVID syndrome are concerns for potential long-term damages. An increasing body of evidence highlights extracellular vesicles' (EVs) relevance in modulating inflammation and cell death in the diseases related to these processes. Several types of EVs-based investigational new drugs against COVID-19 have been approved by the US Food and Drug Administration to initiate a Phase I/II trial under an Investigational New Drug protocol. Due to EVs’ inherent potential in transferring material between cells, their natural origin, and their capability to encapsulate various biological molecules can be employed as natural drug delivery nanoparticle-based systems, offering an exciting alternative for administering drugs acting on the cell cycle control. In this context, small-molecule inhibitors of Mouse Double Minute 2 (MDM2) such as Nutlin-3 and Idasanutlin by promoting p53 survival and its antiviral activity might be helpful to modulate the IFN signalling pathway and reduce the overall pro-inflammatory burden.